Participação do vírus sincicial respiratório, das espécies reativas de oxigênio e da autofagia na formação de redes extracelulares de eosinófilos na asma - Silveira, Josiane Silva (2018)
INTRODUCTION: asthma is a chronic inflammatory disease characterized by secretion of elevated levels of cytokines (interleukin (IL)-4, IL-5 and IL-13), reactive oxygen species (ROS), autophagy and eosinophil extracellular traps (EETs) release in airway. Moreover, respiratory syncytial virus (RSV) infection may facilitate allergic sensitization development as well as exacerbate asthma symptoms. Recently, studies have demonstrated an increase of autophagy in eosinophils of asthmatic patients, contributing to an increase in inflammatory response. In asthma, an increase in EETs release may cause tissue damage and an increase in mucus viscosity, which contribute to airway obstruction and reduction of lung function. However, the mechanism of EETs formation and its pathophysiologic role in asthma are poorly understood. OBJECTIVE: the aim of this dissertation was to elucidate some mechanisms involved in EETs release in asthma. We investigated whether the respiratory syncytial virus (RSV) could induce EETs in vitro in bronchoalveolar lavage fluid (BALF) eosinophils of an experimental asthma model. Moreover, we evaluated ROS and autophagy participation in mechanisms involved in EETs formation. METHODS: in order to perform the experimental model of asthma, BALB/cJ mice were sensitized with two subcutaneous injections of ovalbumin (OVA) on days 0 and 7, followed by three intranasal challenges with OVA on days 14, 15 and 16 of the protocol. In paper 1, BALF eosinophils of OVA group and control group were stimulated with RSV (103 PFU/mL) in vitro for 3 hours. After that, culture supernatant was collected in order to perform the analyses proposed in this study which were evaluated according to the specific objectives of this paper. In paper 2, during the experimental asthma protocol, mice were treated intranasally with a nicotinamide adenine dinucleotide phosphate oxidase (NDPH oxidase) inhibitor, diphenyleneiodonium (DPI), or a glutathione precursor, N-acetylcysteine (NAC). In paper 3, mice were treated intranasally with an autophagy inhibitor, 3-Methyladenine (3-MA). Treatments were performed 45 minutes before of the three intranasal administrations with OVA. At the end of the protocol, BALF and lung tissue were collected to perform the techniques discribed in each of the papers, according to their specific objectives. RESULTS: in paper 1, we verified an increase in EETs release in BALF eosinophils from OVA group stimulated with RSV in vitro. RSV in vitro decreased IFN-γ in BALF cells when compared to the OVA group. In paper 2, we showed that in NAC-treated OVA group there was a decrease in the inflammatory cells in BALF and lung tissue. DPI or NAC treatments reduced EPO activity, goblet cells hyperplasia, inflammatory cytokines and NFĸB p65 immunocontent in lung, and they helped in decreasing ROS production in lung. Furthermore, NAC increased catalase (CAT) activity in lung. However, only NAC treatment improved mitochondrial energy metabolism in lung. We showed that DPI or NAC reduced EETs formation in BALF from the OVA group. In paper 3, we showed that in 3-MA-treated OVA group there was a decrease in the inflammatory cells, EPO activity, goblet cells hyperplasia, inflammatory cytokines, NFκB p65 immunocontent, and oxidative stress in airway. Moreover, 3-MA was able to improve mitochondrial energy metabolism and increase Na+,K+-ATPase activity. We also demonstrated that 3-MA decreased light chain 3B (LC3B) in BALF cells and lung tissue as well as reduced EETs formation in BALF. CONCLUSION: our results verified an important role for RSV in the induction of EETs release. Moreover, DPI, NAC and 3-MA treatments decreased airway inflammation, oxidative stress and EETs release in asthma. Our data suggested that RSV, ROS and autophagy participate in the mechanisms for EETs release in asthma. Thus, identification of mechanisms that regulate EETs formation in asthma may contribute to a better understanding of the pathogenesis of this chronic inflammatory disease which damages patients’ quality of life and is responsible for a high economic cost for the Brazilian Single Health System (SUS).